KAJIAN YURIDIS PERALIHAN HAK ATAS TANAH MILIK ANAK YANG MASIH DI BAWAH UMUR (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
The development of agrarian law in Indonesia regarding the transfer of ownership rights to land through buying and selling has progressed. Based on the facts on the ground, a problem arises when a child who is still underage has land rights and then wants to take legal action on the land, especially the transfer of rights due to buying and selling. Article 1320 of the Civil Code expressly states that an agreement is legally valid if it meets the qualification requirements, while one of the causes of individual legal subjects is declared incompetent if they are underage. This study aims to examine the procedures and methods for transferring rights to land owned by minors. The approach method used in this research is normative juridical and descriptive-analytical. The data used as the main source of data in this study is secondary data. The results of this study indicate that the application for heirs of property rights over minors is granted by the court and the one who acts to make the transfer of rights from the land is the guardian who has been appointed by the court. The determination of guardianship is used as legal evidence of the existence of guardianship guaranteed by the District Court that the minor represented by his guardian to make a sale and purchase is correct and there has been a sale and purchase for the benefit of his heirs.